Risk factors associated with lumpy skin disease in cattle in West Kazakhstan - Issimov, A.; Kushaliyev, K.; Abekeshev, N.; Molla, W.; Rametov, N.; Bayantassova, S.; Zhanabayev, A.; Paritova, A.; Shalmenov, M.; Ussenbayev, A.; Kemeshov, Zh.; Baikadamova, G. (Preventive Veterinary Medicine, 2022)
Lumpy skin disease is an important emerging disease posing a threat to the livestock industry worldwide. Moreover, factors involved in disease transmission in the field and at farm level remain unidentified. This research was based on a cross-sectional study using a questionnaire administered through face-to-face interviews with affected farmers. From January 2021 to July 2021, 543 households were visited in four provinces of the West Kazakhstan region to assess the prevalence of LSD and its associated risk factors. Animal and farm level risk factors were examined using univariable and multivariable mixed effect logistic regression. At animal level, the factors associated with LSD outbreaks include herd size Medium OR = 0.68, (95% CI: 0.54–0.84); large OR = 0.63, (95% CI: 0.49–0.81), purchasing animals OR = 11.67, (95% CI: 8.87–15.35), and selling animals during LSD outbreak OR = 1.24, (95% CI: 1.06–1.45). The overall animal level and herd level LSD prevalence were 10.2% (95% CI: 9.6 −0.10.9) and 49.2% (95% CI: 45.0 – 53.4) respectively. Our study demonstrates the dissemination of LSDV from primary outbreaks to new areas and risk factors associated with LSD in Kazakhstan. This finding will enhance knowledge on disease epidemiology and help develop coordinated actions in prevention and control of the possible LSD outbreaks Нодулярный дерматит является важным новым заболеванием, представляющим угрозу для животноводства во всем мире. Более того, факторы, участвующие в передаче болезни в поле и на уровне фермы, остаются невыясненными. Это исследование было основано на перекрестном исследовании с использованием вопросника, проведенного в ходе личных интервью с пострадавшими фермерами. С января 2021 г. по июль 2021 г. было посещено 543 домохозяйства в четырех областях Западно-Казахстанской области для оценки распространенности ЗУД и связанных с ним факторов риска. Факторы риска на уровне животных и ферм были исследованы с использованием однофакторной и многомерной логистической регрессии со смешанным эффектом. На уровне животных факторы, связанные со вспышками ЗУД, включают размер стада: Средний ОШ = 0,68 (95% ДИ: 0,54–0,84); большое ОШ = 0,63 (95% ДИ: 0,49–0,81), покупка животных ОШ = 11,67 (95% ДИ: 8,87–15,35) и продажа животных во время вспышки ЗУД = 1,24 (95% ДИ: 1,06–1,45) . Общая распространенность ЗУД на уровне животных и на уровне стада составляла 10,2% (95% ДИ: 9,6–0,10,9) и 49,2% (95% ДИ: 45,0–53,4) соответственно. Наше исследование демонстрирует распространение ВЗУД из первичных вспышек в новые районы и факторы риска, связанные с ЗУД в Казахстане. Это открытие расширит знания об эпидемиологии заболеваний и поможет разработать скоординированные действия по профилактике и контролю возможных вспышек ЗУД.
Keywords: скопус; импакт-фактор 2022; научный журнал; зарубежное издание; дальнее зарубежье; периодическое издание; зарубежные авторы; нодулярный дерматит; зко; ветеринария